Stress corrosion behavior of 6082 aluminum alloy - Zhou, Bin; Yang, Li; Yang, Shou‐Bing; Bai, Di; Olugbade, Oluwatobi; Huang, Gen‐Zhe (Materials and corrosion, 2020)
Stress corrosion tests of 6082 aluminum alloy were carried out by using a three‐point bending fixture while holding at 50% of yield strength state through different immersion times in 1.5% NaCl electrolyte solution. The electrochemical impedance spectra and dynamic electric potential polarization curves were measured to indicate the stress corrosion behavior of the alloy. Optical microscopy, scanning electron microscopy, and X‐ray energy spectrum analysis were applied for microstructural investigations. The results show that all of the Nyquist electrochemical impedance spectra consisted of high‐ and low‐frequency double capacitive arcs. However, an increase in immersion time while holding at 50% of yield stress resulted in a corresponding increase in the corrosion current density, leading to gradual corrosion depth growth, and a decrease in the corrosion resistance of the alloy. 6082 Aluminum alloy included AlMnFeSi, Mg2Si, and Si secondary phases. The different secondary phases presented different stress corrosion behaviors. Stress corrosion cracks were generated at the boundaries of AlMnFeSi and matrix or within the AlMnFeSi phase. Crack direction is always perpendicular to the tensile stress applied. Mg2Si secondary phase was self‐corroded as its corrosion potential is lower than that of the matrix. As the electric potential of Si is higher than that of the matrix, corrosion occurred at the matrix side of the boundary between Si and matrix. Stress corrosion tests of 6082 aluminum alloy were carried out by using a three‐point bending fixture while holding at 50% of yield strength state through different immersion times in 1.5% NaCl electrolyte solution. The different secondary phases presented different stress corrosion behaviors. Stress corrosion cracks were generated at the boundaries of AlMnFeSi and matrix or within the AlMnFeSi phase.